THE INFLUENCE OF SOCIAL MEDIA CONTRIBUTION, BRAND AMBASSADOR, SERVICE QUALITY, CONSUMER TRUST, AND BRAND IMAGE ON PURCHASE DECISIONS FOR TELKOMSEL OPERATOR SERVICES - Muhammad Azizi*; Jimi Ronald; Yosi Eka Putri (Universitas Indo Global Mandiri Palembang, 2025)
Objective: This research aims to see the influence of the contribution of social media, brandambassadors, service quality, consumer trust and brand image together on purchasing decisions amongPGRI West Sumatra Economics students.Design/Methods/Approach: This research uses a quantitative type of research. The population in thisstudy were all Economic Education Students Class of 2022 at PGRI University, West Sumatra. Dataanalysis techniques used in this research are Descriptive Analysis, Inductive Analysis, Multiple LinearRegression Analysis, Determination Analysis (R²), Hypothesis Testing.Findings: Based on the data analysis results, the following conclusions can be drawn: 1) Social Media hasa positive and significant effect on Purchase Decision, with a coefficient value of 0.181. 2) BrandAmbassador does not have a significant effect on Purchase Decision, with a coefficient value of 0.044. 3)Service Quality does not have a significant effect on Purchase Decision, with a coefficient value of 0.272.4) Consumer Trust has a positive and significant effect on Purchase Decision, with a coefficient value of0.222. 5) Brand Image does not have a significant effect on Purchase Decision, with a coefficient value of0.074. 6) Social Media, Brand Ambassador, Service Quality, Consumer Trust, and Brand Image togetherhave an effect on Purchase Decision, where F-count (6.090) > F-table (2.317), with a coefficient ofdetermination (R2) value of 0.255. This means that Social Media, Brand Ambassador, Service Quality,Consumer Trust, and Brand Image influence Purchase Decision by 25.50%, with the remaining 74.50%.Originality/Value: This study employs model feasibility tests, namely the Maximum Likelihood Test andthe Ramsey RESET Test. These tests aim to identify the model parameters that are most likely to generatethe observed data and to assess whether the regression model used is correctly specified or suffers fromspecification errors.Practical/Policy implication: This research is beneficial for understanding the influence of Social Media,Brand Ambassadors, Service Quality, Consumer Trust, and Brand Image on the Purchase Decision ofTelkomsel Operator Services. Additionally, it provides insights into the theory of Purchase Decision andthe factors that influence it. Key Words: social media, brand ambassador, service quality, consumer trust, image, purchasing decisions